Keefektifan Penerapan Model Problem Based Learning (PBL) dan Model Learning Cycle 7E (LC7E) serta Integrasinya terhadap Hasil Belajar Ditinjau dari Kemampuan Regulasi Diri dan Kreativitas Siswa - RATNA DEWI KUSUMAWATI; SUCIATI SUDARISMAN; MARIDI MARIDI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
The aims of this research were to know: (1) the effect of learning model (PBL, LC7E, integration with LC7E and PBL) towards learning outcomes; (2) the effect of the high and the low of self-regulation towards learning outcomes; (3) the effect of the high and the low creativity on learning outcomes; (4) the interaction between the learning model with the self-regulation towards learning outcomes; (5) the interaction between learning model with the creativity towards learning outcomes; (6) the interaction between self-regulation with creativity towards learning outcomes; (7) the interaction between learning model with self regulation and creativity towards learning outcomes. This research using experiment method with factorial design 3x2x2. The population of the research was all of the students in X Sains class SMA Negeri 2 Karanganyar for the first semester 2013/2014. The sample of the research was determined by cluster random sampling technique that consisted of three classes. The first experiment class was treated using PBL model, the second experiment class was treated using LC7E model, the third experiment class was treated using integration PBL and LC7E model. The test technique for collected data student’s achievement of the cognitive. The non-test technique by questionnaire for the ability self-regulation data, creativity, psychomotor aspects, affective aspects and observation sheets for affective and psychomotor aspects. The research hypothesis was analyzed with unequal cell number using software SPSS 18. The research result showed that: (1) There is effect between PBL model, LC7E model, integration of model PBL and LC7E towards learning outcomes of cognitive, affective, psychomotor; (2) there is effect between self-regulation towards cognitive; (3) there is effect between creativity towards the cognitive and affective; (4) no interaction between PBL model, LC7E model, integration of model PBL and LC7E, with self-regulation on learning outcomes of cognitive, affective and psychomotor; (5) no interaction between PBL model, LC7E model, integration of PBL and LC7E model with creativity on learning outcomes of cognitive, affective and psychomotor; (6) no interaction between self-regulation with creativity on learning outcomes of cognitive, affective and psychomotor; (7) no interaction between PBL model, LC7E model, integration of PBL and LC7E model with self-regulation and creativity on learning outcomes of cognitive, affective, psychomotor.